Low Dosage Regional Anesthesia for Bladder Tumors in Aortic Stenosis Patient - Pinem, Emmysri Ninta Karina B.; Thedja, Maha Swardwipayana Putra; Poddala, Max Norman; Dharmayana, Ida Bagus Gede Dwi (JAI (Jurnal Anestesiologi Indonesia), 2025)
Background: Aortic stenosis (AS) is a narrowing of the heart's aortic valve. The most common cause of AS in adults is degenerative calcification of the aortic valve, which increases with age.Most patients with AS experience gradual increase in obstruction over many years and will remain asymptomatic until the 6th to 8th decade of life. The prognosis being poor when symptoms appear. Patients with AS present a challenge of hemodynamic disturbance for anesthesiologists. The use of regional anesthesia in patients with severe AS is contraindicated because of the sympatholytic effect which causes loss of vascular tone and a significant reduction in cardiac output.Case: A 77 years old male with a height of 155 cm and a weight of 35 kg with moderate aortic stenosis (EF 65%), ventricular heart disease (VHD), hypertensive heart disease (HHD), heart failure (HF) with therapy, underwent bladder tumor surgery with low dose regional anesthesia using bupivacaine 0.5% heavy 7.5 mg (1.5 ml) with adjuvant fentanyl 25 mcg with total volume 2 ml regional block was achieved within 5 minutes and hemodynamically stable perioperatively. There was no acute HF or worsening of postoperative hemodynamics.Discussion: The main principle of anesthesia in AS patient is to avoid tachycardia, maintain sinus rhythm and avoid a decrease in systemic vascular resistance (SVR) which will cause compensation in the form of an increase in heart rate, thereby making the heart work harder, avoiding hypovolemia and fluid overload.Conclusion: Low dose regional anaesthesia can become an option. In cases of AS due to fewer side effects, with more stable haemodynamics compare with convensional regional anaesthesia. This condition may need furthere studies.